2012
DOI: 10.1021/pr300487s
|View full text |Cite
|
Sign up to set email alerts
|

Satiety Hormone and Metabolomic Response to an Intermittent High Energy Diet Differs in Rats Consuming Long-Term Diets High in Protein or Prebiotic Fiber

Abstract: Large differences in the composition of diet between early development and adulthood can have detrimental effects on obesity risk. We examined the effects of an intermittent high fat/sucrose diet (HFS) on satiety hormone and serum metabolite response in disparate diets. Wistar rat pups were fed control (C), high prebiotic fiber (HF) or high protein (HP) diets (weaning to 16 weeks), HFS diet challenged (6 weeks), and finally reverted to their respective C, HF, or HP diet (4 weeks). At conclusion, measurement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 33 publications
2
28
1
Order By: Relevance
“…Furthermore, improved oGTT could not be accounted for by differences in body weight gain or body fat amongst the groups. In contrast, male Wistar rats, following a high fibre diet (21% w/w) comprising inulin and oligofructose, had a lower percentage of body fat (Reimer et al 2012). In our study, we failed to detect a significant change in body composition, which may be related to the short length of our study (10 weeks) versus that of Reimer et al (2012) (21 weeks).…”
Section: Figcontrasting
confidence: 82%
“…Furthermore, improved oGTT could not be accounted for by differences in body weight gain or body fat amongst the groups. In contrast, male Wistar rats, following a high fibre diet (21% w/w) comprising inulin and oligofructose, had a lower percentage of body fat (Reimer et al 2012). In our study, we failed to detect a significant change in body composition, which may be related to the short length of our study (10 weeks) versus that of Reimer et al (2012) (21 weeks).…”
Section: Figcontrasting
confidence: 82%
“…The interest into the adequacy and safety of commercially available pet foods has been growing worldwide [66]. Functional foods such as prebiotics, for example, inulin, gluco-oligosaccharides, and galacto-oligosaccharides have shown to induce beneficial effects on biochemical parameters improving satiety and reducing postprandial glucose and insulin concentrations, thus reducing diabetes-related disorders [67][68][69]. Inulin and oligofructose, but also dietary fibers, can also modify the intestinal microflora in pets and humans by promoting commensal bacteria growth [70][71][72].…”
Section: The "Market Stand" Of Functional Pet Foodsmentioning
confidence: 99%
“…It has been found that the body fat in rats fed with a diet high in prebiotics was significantly lowered than the ones fed with a diet high in protein and control diet [28]. In similar studies on humans, it has also been shown that the increase in prebiotics intake was associated with weight loss due to a decrease in energy intake [11,29].…”
Section: Body Weight Managementmentioning
confidence: 99%